Policymaking in data poor countries: measuring the Lebanese political agenda in a new data set. - Mahmalat, Mounir (International Development Planning Review, 2020)
This article introduces a novel data set on legislative activity in Lebanon covering all important primary and secondary legislation between 1950 and 2016. It analyses the data set based on agenda-setting theory and traces patterns of political attention across policy areas and over time. The article shows how legislation data can offer important insights into the political agenda of countries whose legislative institutions provide little data on their workings. In this way, the creation of the data set ties in with increasing scholarly attention to governance issues in the Middle East and North Africa. Moreover, the article contributes to the study of political attention by proposing to identify important legislation based on reviews of legal experts.